Numerical investigation of the optimum cushioning properties of insole materials: the effect of subject-specific geometry and loading - Chatzistergos, Panagiotis; Naemi, Roozbeh; Chockalingam, Nachiappan (Footwear science, 2015)
Footwear Science Numerical investigation of the optimum cushioning properties of insole materials: the effect of subject-specific geometry and loading